Respuesta :
Alright this one is just kinematics, you can use one of the big four equations and in this case this one works because acceleration is constant and you don’t have the final velocity to worry about:
Δx= displacement
Vi= initial velocity
T= time
A= acceleration
Δx=(Vi)(t)+(1/2)(a)(t^2)
A=9.8m/s2
Vi=8.49 m/s
Δx=2.89 meters
Then plug in:
2.89=(8.49)(t)+(1/2)(9.8)(t^2)
Then solve for t and you’re all set.
Δx= displacement
Vi= initial velocity
T= time
A= acceleration
Δx=(Vi)(t)+(1/2)(a)(t^2)
A=9.8m/s2
Vi=8.49 m/s
Δx=2.89 meters
Then plug in:
2.89=(8.49)(t)+(1/2)(9.8)(t^2)
Then solve for t and you’re all set.
Answer:
0.465 seconds (Answer containing 3 significant figures)
Explanation:
Vi = 8.49
DeltaY = 2.89
A = -9.8
T = ?
Vf = Unknown
First Solve for Vf
Vf^2 = Vi^2 + 2aDeltaY
Vf = SQRT 8.49^2+2(-9.8)(2.89)
Vf = 3.93 m/s
Now find t
Vf = Vi + at
3.93 = 8.49 + (-9.8)(t)
= 0.4653
= 0.465 s